Night shift - King, Stephen, 1947- (New York : Signet, 1979)
A collection of nineteen horror stories, including "Jerusalem's Lot," "Graveyard Shift," "Battleground," "The Lawnmower Man," "Sometimes They Come Back," and "The Last Rung on the Ladder.".
Booklist.
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Adult
Keywords: Horror fiction; Short stories